2023
DOI: 10.2169/internalmedicine.0072-22
|View full text |Cite
|
Sign up to set email alerts
|

Lambert-Eaton Myasthenic Syndrome Recurrence Induced by Pembrolizumab in a Patient with Non-small-cell Lung Cancer

Abstract: A 73-year-old woman in complete remission from localized small-cell lung cancer associated with Lambert-Eaton myasthenic syndrome (LEMS) 22 years earlier was referred to our hospital and diagnosed with non-small-cell lung cancer. After three courses of pembrolizumab, an immune checkpoint inhibitor, the patient complained of muscle weakness, fatigue, ptosis, and dysarthria. The anti-voltage-gated calcium channel antibody level was elevated, and waxing was observed on a high-frequency repetitive stimulation test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…To our knowledge, there were only four malignant cases who had preexisting LEMS but had Durvalumab for Lambert-Eaton Syndrome J Med Cases. 2023;14(2):71-75 been treated by ICIs [7][8][9][10]. These rare cases suggest that ICI is a possible treatment option for cancer patients with LEMS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, there were only four malignant cases who had preexisting LEMS but had Durvalumab for Lambert-Eaton Syndrome J Med Cases. 2023;14(2):71-75 been treated by ICIs [7][8][9][10]. These rare cases suggest that ICI is a possible treatment option for cancer patients with LEMS.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, combined immunochemotherapy did not exacerbate the preexisting LEMS. To our knowledge, there were only four malignant cases who had preexisting LEMS but had been treated by ICIs [ 7 - 10 ]. These rare cases suggest that ICI is a possible treatment option for cancer patients with LEMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takigawa et al 28 reported an interesting single case of LEMS reoccurrence in a 73-year-old woman treated with pembrolizumab. She had limited-stage SCLC with LEMS 22 years earlier and had been in remission after chemoradiation.…”
Section: Lambert–eaton Myasthenic Syndrome (Lems)mentioning
confidence: 99%
“…There were several other cases of LEMS with renal cell CA and SCLC in patients receiving ipilimumab, nivolumab, and pembrolizumab, but the ROR was 5-7, and the authors did not consider it to be significantly disproportional. 27 Takigawa et al 28 reported an interesting single case of LEMS reoccurrence in a 73-yearold woman treated with pembrolizumab. She had limited-stage SCLC with LEMS 22 years earlier and had been in remission after chemoradiation.…”
Section: Lambert-eaton Myasthenic Syndrome (Lems)mentioning
confidence: 99%